Severe Bushmaster Snakebite Envenoming: Case Report and Overview - Garces-Filho, Allan Quadros; Santos, Humberto H. M.; Aguiar, Thays K. P. P.; Ramos, Dafnin L. S.; Galan, Luis E. B.; Dantas, Domingos S. M.; Cerni, Felipe A.; Carbonell, Roberto C.; Pucca, Manuela B. [UNESP] (Mdpi, 2024)
Unlike the well-documented bothropic and crotalid snakebites in Brazil, lachetic envenomings (i.e., triggered by the bushmaster snake) are rare and present significant diagnostic challenges. This case describes a severe envenoming induced by a Lachesis muta snake in a 26-year-old Brazilian man who was bitten near a forest in November 2022. Characteristic symptoms such as sweating and bradycardia pointed towards lachetic envenoming, but initial misdiagnosis as a bothropic bite resulted in a delay in appropriate antivenom therapy. Despite later receiving the correct treatment, the severity of the envenoming necessitated the amputation of a finger and triggered a severe infection. This report highlights the challenges of diagnosing and treating Lachesis spp. bites due to their rarity. Moreover, an overview of lachetic-induced signs and symptoms was explored. This study emphasizes that further reports are warranted to improve understanding of Lachesis muta envenoming and to optimize treatment strategies.
Keywords: snakebite envenoming; Lachesis; Roraima; infection; amputation